TABOO LANGUAGE EXPRESSION BETWEEN SELLER AND BUYER IN TRADITIONAL MARKET - WIDYA NOLA SAMOSIR; MEISURI MEISURI; CITRA ANGGIA PUTRI (State University of Medan, 2020)
This research discussed about taboo language in Batak Toba language at Pajak Sore Padang Bulan Medan which aimed to find out the types, the impacts of taboo language expression towards customers, and how Bataknese society perceptions towards their taboo language. This research was based on Mahmoud’s theory. This research was conducted by using descriptive qualitative method. The data were taken from 25 conversations of male and female participants who become sellers and customers in Traditional Market. The findings showed that there were 25 data, 20 data for the types and the impacts, 5 data for Bataknese society perceptions. The dominant types from taboo words in Batak Toba language is Insult and Slurs with 7 expressions, second is scatology with 5 expressions, followed by epithets with 3 expressions, vulgarity with 1 expression, obscenity with 1 expression. Batak sellers is the dominant use taboo language because it was their habit when they were angry but sometimes it is also a part of their close relationship, it means that how close their relationship, so they can used the taboo language. In the analyzed of the impacts of taboo language towards customers, the dominant impacts were people got offended easily and sometimes they become the people who have the irrational thinking. There were 5 perceptions of Bataknese society perceptions about their taboo language and the dominant perception were sellers and customers could not receive taboo words because they still thought that the language could have a bad impact on children because they would replicate and pronounce the taboo language.